Mental disorders in patients with cystic fibrosis - A. A. Klimenko; A. Yu. Aleksandrova (Klinicist)
Introduction. Cystic fibrosis (CF) is a genetic disease that leads to dysfunction of internal organs and significantly increases the risk of respiratory infections. According to the N. P. Bochkov Medical and Genetic Research Center, 1 out of 9,000 newborns suffers from CF. Chronic disease has a negative impact on mental health and can contribute to the developmentof anxiety and depressive disorders, as well as accentuated traits and personality disorders.   Aim. To summarize the currently available data on mental disorders in patients with CF, as well as to summarize current recommendations regarding the management of patients with this disease.   Materials and methods. Articles were searched in Google Scholar databases, eLIBRARY.ru, Elsevier, PubMed from 2014 to 2024 by key words in Russian and English in accordance with the purpose of the study.   Results. It has been established that mental health problems are associated with worse compliance to the treatment, as well as difficulties with self-organization and self-care. Some hypotheses that explain the pathogenesis of mental disorders have been provided. The key characteristics of course and clinical presentation of mental disorders in this group of patients have been described. Some potential recommendations for the treatment are provided, taking into the account the specificities of the metabolism of psychotropic drugs in people with CF. The tactics of management, including the creation of a multidisciplinary team that would consist of a doctor of somatic profile, psychiatrist and a psychologist. A strategy for development of this aspect of medical care for patients with CF has also been proposed.   Conclusion. Drawing the attention of the scientific community to the problem of mental disorders in patients with CF will allow the introduction of methods for monitoring mental status and early detection of symptoms, and will also entail the creation of multidisciplinary teams, including a psychiatrist and a medical psychologist.